Could dysregulation of RASSF1 expression be a mechanism of tumorigenesis in CTVT? - Fêo,Haline B. (2022)
ABSTRACT: Canine transmissible venereal tumor (CTVT) is the oldest known somatic cell lineage. It is a transmissible cancer that propagates naturally in dogs and reportedly contains gene mutations. RASSF1 participates in DNA damage repair, and its downregulation, results in tumor progression. Hence, RASSF1 is a tumor suppressor gene. Its expression was quantified in tumors from seventeen animals and three cell cultures derived from tumors. In general, RASSF1 was underexpressed in 65%, and absent in 35% of tumor samples. Cells from tumor tissue cultures showed decreased expression of RASSF1 in 67% and elevated expression in 33% of samples tested. The tumor tissues showed significantly lower levels of RASSF1 expression compared to cultured cells. Previously we reported that both the tumor microenvironment and the host immune system appear to influence the tumorigenesis and stage of CTVT. This is the first article to demonstrate the expression of RASSF1 in CTVT. Decreased RASSF1 possibly helps tumor progression.